Development of acute toxicity tests on Daphnia magna for the determination of polycyclic aromatic hydrocarbons (PAHs) and phthalates in soft plastic baits - Alexander Ghrim (2020)
Marine litter is a global problem that has been gaining attention in recent years. It threatens flora and fauna of sensible ecosystems. The major part of this litter is plastic material which is hardly degradable. Generally, the main diffuse input pathways are from landside sources or through rivers. Microplastic particles are found nearly everywhere nowadays, yet in deep sea. The recreational fishing industry plays a part in this issue. Angler often make use of soft plastic lures. It is disputed that they have direct impacts on limnic and marine ecosystems. However, they have indirect impacts, because they include additives like softeners or attractants. These substances and other hazardous compounds might be released during fishing. In this thesis, two compound classes are examined. Polycyclic aromatic hydrocarbons have toxicologic properties as being carcinogenic, mutagenic or teratogenic. Low-molecular phthalates are suspected to be endocrine disruptive. They were chosen as pollutants, because they both tend to be persistent and easily bioaccumulate. Their possible effects on the species Daphnia magna were investigated in this study. Besides, two methods on how to test soft plastic material in acute toxicity tests on Daphnia magna were developed and evaluated with two different soft plastic lures. The developed plastic contact test method uses pestled plastic material debris. Dilution medium is added to it and everything is shaken for up to 24 hours. The fact that the material is not removed during testing leads to a constant release of pollutants. Contrary, leaching test uses 1 cm2 great cubes which are also shaken for one day in dilution medium. However, the material is removed before start and only the leaching water is used in this toxicity test method. EC50 concentrations of 48 hours acute toxicity tests show that plastic lure Tiddler has greater effects on daphnids than Möhrchen. Additionally, gas chromatography analysis of these samples confirms this fact and suggests that hardly soluble phthalates emit easier due to solvents on or in the plastic material. Another aspect is the toxic effect addition of these determined substances. However, PAH values should be treated with caution, because only a few reached the limit of quantitation. Moreover, average standard deviation values depict a greater stability and validity of plastic contact test compared with leaching test method. Considering the applicability with other materials, the plastic contact test is time consuming but more realistic and provides reliable results.